Analisis Rantai Pasok Berbasis Keramba Jaring Apung Menggunakan Scor di Karimun Jawa - Arismawati, Paramaditya; Agnia , Nilna (Green Publisher Indonesia, 2025)
The increasing demand for high-value fishery commodities in the waters of Central Java highlights the significant economic potential of cantang grouper aquaculture based on Floating Net Cages (Keramba Jaring Apung/KJA) in Karimun Jawa. However, due to the complexity of the cultivation process—ranging from seed and feed procurement, fish maintenance, to harvest distribution—an effective and flexible supply chain system is required. This study aims to map and analyze the supply chain of cantang grouper aquaculture using the Supply Chain Operations Reference (SCOR) framework to identify critical points in the operational flow and to formulate improvement recommendations based on the 5W+1H principle. The research method involves field interviews and observations, as well as structural analysis of the supply chain from upstream to downstream, covering the five main SCOR processes: Plan, Source, Make, Deliver, and Return. The results reveal critical issues in inaccurate planning of seed and feed requirements, unstable input quality, fish health management, timeliness of delivery, and responsiveness to non-conforming products. The proposed improvements include data-driven planning systems, strategic partnerships with suppliers, utilization of IoT technology for water quality monitoring, logistics digitalization, and application-based quality reporting. This study contributes to the development of a more adaptive and sustainable supply chain model in the context of marine aquaculture and addresses a gap in the literature, which has predominantly focused on fish processing industries. Future research may incorporate performance measurement using SCOR indicators reliability, responsiveness, agility, asset, and cost—and integrate risk identification and mitigation strategies.